Improving Learning Outcomes of Chemistry Subjects through the Application of the Guided Inquiry Learning Model - Afriana, Linda (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to improve students’ chemistry learning outcomes through guided inquiry learning models in class XI IPA 1 SMA Negeri 1 Tanjung Batu. This research is classroom action research carried out in three cycles. Data collection was carried out using a test at the end of the cycle. From the research, it was found that the completeness of students’ learning outcomes before the action (T0) was 26.67% with an average grade of 59.83. After being given action by using the guided inquiry learning model (T1) the mastery of learning outcomes and the average value of learning outcomes increased to 53.33% and 64.33. Then in cycle 2 (T2) learning completeness increased to 66.67% with an average grade of 75.58. Whereas in cycle 3 (T3) there was an increase to 86.67% with a class average value of 82.16. The results showed that there was an increase in students’ chemistry learning outcomes by using the guided inquiry learning model, with this model students could find their own knowledge, learning was more meaningful so that learning outcomes could increase. It can be concluded that the use of guided inquiry learning models can improve students’ chemistry learning outcomes, where T3>T2>T1>T0. In connection with the research that has been done, the researcher suggests that teachers should apply the guided inquiry learning model if students’ chemistry learning outcomes are low.